Viability of pollen grains and stigma receptivity in Desert Rose - Souza, Cristiane Gonçalves; Ramos, Sabrina Maihave Barbosa; Nietsche, Silvia; Possobom, Clivia Carolina Fiorilo; Almeida, Elka Fabiana Aparecida; Pereira, Marlon Cristian Toledo (Ornamental Horticulture, 2021)
Adenium obesum (Forssk.) Roem. & Schult., popularly known as desert rose, has become a valuable ornamental plant. In floriculture, the production of hybrids is prioritized. Hence, knowledge on floral biology and sexual reproduction of the target species is fundamental. The objectives of this study were: (1) to test sucrose concentrations and temperatures for in vitro germination of A. obesum pollen grains; (2) to identify the effect of temperature on the viability of A. obesum pollen grains; and (3) to evaluate the viability of pollen grains and stigma receptivity in pre-anthesis, at flower opening, and 72 h post-flower opening in three accessions of A. obesum. A significant relationship between temperatures and sucrose concentrations was observed in the in vitro germination test. The highest percentage of in vitro germination of pollen grains, 39.81%, was observed at an estimated temperature of 26.05 °C. Desert rose accessions maintained in biochemical oxygen demand (BOD) chambers at 30 °C during a 16-h light photoperiod showed faster flowering, and temperatures ≥ 25 °C induced pollen grain viability percentages above 69%. Temperature is one of the most important abiotic factors, influencing mainly in pollen germination, pollen tube growing and in efficiency fertilization. The ICA-wd accession stood out and can be considered a pollen donor in artificial pollination. The stigmas of flowers were receptive from a day before flower opening until three days after. The two parameters presented above, stigma receptivity and pollen viability, allow inferences about the appropriate time for successful pollination and subsequent fertilization in desert roses.